Economic and financial valuation of the marble industry in Egypt - Haggag, Farah Ahmed (AUC Knowledge Fountain, 2012)
This study is mainly to evaluate economically and financially the whole marble industry in Egypt. An industrial analysis on the marble industry is done which includes: summary on the international market of marble, sector and enterprises' structure, nature of competition, pricing, and differentiated marble and granite products in the local market. Also, a cluster analysis on the marble cluster is done that comprise: the marble cluster map, the marble cluster diamond, the five forces that shape industry competition, and competitive analysis. A financial valuation is conducted on the marble supply chain divided to the extraction and processing using an investment appraisal approach. The financial valuation includes: revenue cost analysis, estimation of capital investments, cash flow analysis, net present value, CAPM model, and profitability ratios. Afterwards, an economic valuation is done for the marble extraction and processing that incorporates economic cost and benefit analysis, economic investment requirements, industrial positive and negative externalities, natural resource depletion and sustainability using Hotelling's rent, net economic present value, and economic contributions. Based on the results, the main recommendations are: imposition of a Pigouvian tax of 36% on the marble quarries, removal of export duty on marble raw materials, and linking between marble extraction and processing rather than focusing on exporting extraction.